Validating Gameplay Activity Inventory (GAIN) for Modeling Player Profiles - Jukka Vahlo; Jouni Smed; Aki Koponen (Springer, 2025)
In the present study, we validated Gameplay Activity Inventory (GAIN), a short and psychometrically sound instrument for measuring players' gameplay preferences and modeling player pro les. In Study 1, participants in Finland (N = 879) responded to a 52-item version of GAIN. An exploratory factor analysis was used to identify ve latent factors of gameplay activity appreciation: Aggression, Management, Exploration, Coordination, and Caretaking. In Study 2, respondents in Canada (N = 1; 322) and Japan (N = 1; 178) responded to GAIN, and the factor structure of a 15-item version was examined using a Con rmatory Factor Analysis. The results showed that the short version of GAIN has good construct validity, convergent validity, and discriminant validity in Japan and in Canada. We demonstrated the usefulness of GAIN by conducting a cluster analysis to identify player types that differ inboth demographics and game choice. GAIN can be used in research as a tool for investigating player pro les. Game companies, publishers and analysts can utilize GAIN in player-centric game development and targeted marketing and in generating personalized game recommendations.